(untitled) - Roberts, Royston M. (New York, 1989)
Contents: What do Velcro, penicillin, X rays, Teflon, dynamite, and the Dead Sea Scrolls have in common? Serendipity! These diverse things were discovered by accident, as were hundreds of other things that make everyday living more convenient, pleasant, healthy, or interesting. All have come to us as a result of serendipity--the gift of finding valuable or agreeable things not sought for or "the faculty of making fortunate and unexpected discoveries by accident"
Keywords: Serendipity in science,Tầm quan trọng của khoa học